Eco-smart biocontrol strategies utilizing potent microbes for sustainable management of phytopathogenic diseases - Ihtisham Ul Haq; Kashif Rahim; Galal Yahya; Bushra Ijaz; Sajida Maryam; Najeeba Parre Paker (Biotechnology Reports)
Plants have an impact on the economy because they are used in the food and medical industries. Plants are a source of macro- and micronutrients for the health of humans and animals; however, the rise in microbial diseases has put plant health and yield at risk. Because there are insufficient controls, microbial infections annually impact approximately 25 % of the world's plant crops. Alternative strategies, such as biocontrol, are required to fight these illnesses. This review discusses the potential uses of recently discovered microorganisms because they are safe, effective, and unlikely to cause drug resistance. They have no negative effects on soil microbiology or the environment because they are environmentally benign. Biological control enhances indigenous microbiomes by reducing bacterial wilt, brown blotch, fire blight, and crown gall. More research is required to make these biocontrol agents more stable, effective, and less toxic before they can be used in commercial settings.